2021
DOI: 10.1038/s41577-020-00488-6
|View full text |Cite
|
Sign up to set email alerts
|

Local and systemic mechanisms linking periodontal disease and inflammatory comorbidities

Abstract: Periodontitis, a major inflammatory disease of the oral mucosa, is epidemiologically associated with other chronic inflammation-driven disorders, including cardio-metabolic, neurodegenerative and autoimmune diseases and cancer. Emerging evidence from interventional studies indicates that local treatment of periodontitis ameliorates surrogate markers of comorbid conditions. The potential causal link between periodontitis and its comorbidities is further strengthened by recent experimental animal studies establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
743
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 842 publications
(764 citation statements)
references
References 161 publications
(274 reference statements)
7
743
0
14
Order By: Relevance
“…First, this group of athletes has a thorough and continuous medical follow-up, though oral health seems somehow neglected, and this fact has been previously highlighted [ 22 ]. Second, the systemic consequences of periodontitis, for instance the leukocytosis and mild anemia [ 26 ], the increase in inflammatory mediators (CRP and cytokines) [ 27 , 28 ] and harmful consequences for health [ 29 ] may place these athletes at higher risk. Unfortunately, to date, the number of studies on the systemic effect of periodontitis in elite athletes is scarce and further studies are needed to clarify this topic.…”
Section: Discussionmentioning
confidence: 99%
“…First, this group of athletes has a thorough and continuous medical follow-up, though oral health seems somehow neglected, and this fact has been previously highlighted [ 22 ]. Second, the systemic consequences of periodontitis, for instance the leukocytosis and mild anemia [ 26 ], the increase in inflammatory mediators (CRP and cytokines) [ 27 , 28 ] and harmful consequences for health [ 29 ] may place these athletes at higher risk. Unfortunately, to date, the number of studies on the systemic effect of periodontitis in elite athletes is scarce and further studies are needed to clarify this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that oral gut bacteria are associated with the pathogenesis of IBD [47,48]. It has been reported that oral resident bacteria, such as Fusobacteriaceae and Pasteurellaceae, are accumulated in the intestinal mucosa of patients with IBD [49,50].…”
Section: Alteration Of the Microbial Composition In Ibdmentioning
confidence: 99%
“…It has been estimated that a patient with periodontitis experiences several occasions of bacteremia each day lasting for a total up to 3 hours [ 3 ]. Furthermore, a patient with periodontitis can have a wound bed estimated to cover a surface area of 8–20 cm 2 [ 34 ] from which bacteria have easy access to the blood stream [ 20 ]. Bacteria from periodontitis can also be transferred to the brain via other routes such as the trigeminal nerve, circumventricular organs, perivascular spaces, and by olfactory unsheathing cells acting as Trojan horses [ 20 ].…”
Section: Relationship Between Periodontitis and Alzheimer’s Diseasementioning
confidence: 99%